Digital Dramaturgy: Raffi Ahmad's Identity Formation and Privacy Management on Instagram: Dramaturgi Digital: Pembentukan Identitas dan Pengelolaan Privasi Raffi Ahmad di Instagram - Brameswari, Zhafira Adenia; Kartika, Mas Aldrin Zagna Rania (Procedia of Social Sciences and Humanities, 2025)
This research discusses the digital dramaturgy strategy of Raffi Ahmad, a prominent figure in Indonesia. It investigates how he shapes his identity as a star, businessman, and family man, and manages his privacy on the Instagram platform. The research focuses on his online identity formation, audience management while maintaining his authenticity, and the opportunities and challenges he faces regarding privacy and participatory surveillance. Various theories and concepts such as online identity formation, parasocial relationships, context collapse, and privacy and participatory surveillance are used to explain this phenomenon. The purpose of this research is to explain effective strategies for public figures to manage their digital identities.